2018
DOI: 10.1371/journal.pone.0204118
|View full text |Cite
|
Sign up to set email alerts
|

Urban-rural difference in the associations between living arrangements and the health-related quality of life (HRQOL) of the elderly in China—Evidence from Shaanxi province

Abstract: BackgroundSo far limited evidence exist comparing the difference between urban and rural elder residents in relation to how living arrangements correlates to health-related quality of life(HRQOL) of the elderly.ObjectiveThis study aims to compare the HRQOL of the elderly with four living arrangements: living with spouse only (LS), living alone (LA), living with a spouse and adult children(LSC) and the single elderly living with adult children (SLC) in urban and rural areas of China.MethodsThe data were drawn f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 46 publications
7
32
1
2
Order By: Relevance
“…Marital status and living arrangement are other important factors influencing the mental health of the elderly. Our study showed that single/divorced/widowed persons and those living alone were more likely to suffer from mental problems, which are consistent with the findings from other studies [30,32,33]. In addition, this may be attributed to the changes of family structure from a multi-child family to a single-child one.…”
Section: Discussionsupporting
confidence: 92%
“…Marital status and living arrangement are other important factors influencing the mental health of the elderly. Our study showed that single/divorced/widowed persons and those living alone were more likely to suffer from mental problems, which are consistent with the findings from other studies [30,32,33]. In addition, this may be attributed to the changes of family structure from a multi-child family to a single-child one.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, we found significant sex differences in HRQoL, with women reporting better mental health than men. These results are similar to those of previous studies in China and South Korea, 25,26 which found that men are more likely to report poor mental health. In our study, we observed a difference in MCS but not in PCS, which may stem from demographic factors and the distribution of chronic conditions.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, Konnopka and Koeing [12] observed significant associations between age and the EQ-5D-5L dimensions of "morbidity" and "self-care." In terms of living alone, one study analyzed the associations between living arrangement and HRQoL, revealing that HRQoL among older adults living alone or with adult children was worse than those living with a spouse in an urban area [37]. In addition to living alone, quality of care and support is also associated with HRQoL [26].…”
Section: Discussionmentioning
confidence: 99%